2002
DOI: 10.1016/s0304-3959(02)00295-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between resting blood pressure and acute pain sensitivity in healthy normotensives and chronic back pain sufferers: the effects of opioid blockade

Abstract: Resting blood pressure is inversely correlated with acute pain sensitivity in healthy normotensives. This study tested: (1) whether endogenous opioid activity is necessary for this adaptive relationship to occur, (2) whether this relationship is altered in chronic low back pain (LBP), and (3) whether endogenous opioid dysfunction underlies any such alterations. Fifty-one pain-free normotensives and 44 normotensive chronic LBP sufferers received opioid blockade (8 mg naloxone i.v.) or placebo blockade (saline) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
127
3
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(155 citation statements)
references
References 62 publications
23
127
3
2
Order By: Relevance
“…Finally, although prior work suggests that blood pressure-related analgesia may be impaired in chronic pain patients (Bragdon et al 2002;Bruehl et al 2002;Bruehl and Chung 2004), the current findings indicate that some patients do exhibit effective blood pressure-related anal-gesia. These contrasting findings could reflect key methodological differences across these studies.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Finally, although prior work suggests that blood pressure-related analgesia may be impaired in chronic pain patients (Bragdon et al 2002;Bruehl et al 2002;Bruehl and Chung 2004), the current findings indicate that some patients do exhibit effective blood pressure-related anal-gesia. These contrasting findings could reflect key methodological differences across these studies.…”
Section: Discussioncontrasting
confidence: 77%
“…From a "person × situation" perspective, it perhaps may have been more appropriate to examine links between pain catastrophizing and chronic pain using interviews probing for difficulties adjusting to pain, interference with social and work functioning, issues of loss and so forth. The ability to test whether catastrophizing affects pain through physiological reactivity may have been limited because of the unrestricted topics patients could describe in the interviews.Finally, although prior work suggests that blood pressure-related analgesia may be impaired in chronic pain patients (Bragdon et al 2002;Bruehl et al 2002;Bruehl and Chung 2004), the current findings indicate that some patients do exhibit effective blood pressure-related anal-gesia. These contrasting findings could reflect key methodological differences across these studies.…”
contrasting
confidence: 77%
“…In humans, the evidence in favour of opioid dysfunction is mostly negative (e.g., Bruehl et al, 2002;France et al, 2005;Ring et al, 2007;Schobel et al, 1998;cf. McCubbin and Bruehl, 1994;McCubbin et al, 2006) whereas the evidence for baroreceptor activation is more mixed (e.g., al 'Absi et al, 2005;Edwards et al, 2001Edwards et al, ,2003aGuasti, Zanotta, Mainardi, et al, 2002;McIntyre et al, 2006;Rau et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…20,38 These results are supported by human studies that showed that small doses of naloxone (blocking for the most part ÎŒ opioid receptors) 17 are able to reverse AT but not CT analgesia. 1,8,15,19,24,37,44 Alternately, large doses of naloxone (which are believed to ensure adequate blockage of all opioid receptor subtypes) 3,5 were shown to reverse CT analgesia. 23 The interaction between AT and opioids (but not between CT and opioids) observed in the present study indirectly confirm these observations.…”
Section: Acupuncture-like Tens In Opioid Treated Patients 13mentioning
confidence: 99%